1994
DOI: 10.1128/iai.62.4.1282-1288.1994
|View full text |Cite
|
Sign up to set email alerts
|

A murine monoclonal antibody defines a unique epitope shared by Klebsiella lipopolysaccharides

Abstract: A hybridoma secreting a monoclonal antibody (MAb) directed against Klebsiella lipopolysaccharide (LPS) was derived from spleen cells of mice immunized with a smooth, nonencapsulated Klebsiella strain (Friedlander 201; serogroup 01). The MAb, called V/9-5 (immunoglobulin G2a), cross-reacted with LPS preparations produced from reference strains for the Klebsiella 0 serogroups 01, 02ab, 02ac, 03, 04, 05, and 012. Furthermore, the MAb reacted with LPSs from serogroup reference strains 06/08, 09, and 011, which are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1
1

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 47 publications
1
17
1
1
Order By: Relevance
“…These findings confirm earlier observations by Ørskov, who showed that strains in which only parts of the O2a antigen are expressed may exist (36). Three hundred thirty-eight of 378 isolates (89.4%) reacted with MAb V/9-5, which confirms our previous observation that ϳ10% of clinical Klebsiella strains lack the genus-specific core epitope (45). Nineteen of 40 nonreactive strains were found in the O1 serogroup (Table 4).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…These findings confirm earlier observations by Ørskov, who showed that strains in which only parts of the O2a antigen are expressed may exist (36). Three hundred thirty-eight of 378 isolates (89.4%) reacted with MAb V/9-5, which confirms our previous observation that ϳ10% of clinical Klebsiella strains lack the genus-specific core epitope (45). Nineteen of 40 nonreactive strains were found in the O1 serogroup (Table 4).…”
Section: Resultssupporting
confidence: 90%
“…MAbs. MAb Ru-O1, specific for Klebsiella O1 LPS, and MAb V/9-5, specific for a Klebsiella genus-specific antigen located in the outer core region of LPS, have been described previously (39,45). MAb IV/4-5 was obtained by the same methods except that strain 7380 (O2ab:KϪ) was used for immunization of mice.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preliminary NMR data show that O-specific polysaccharides, obtained after deamination of LPSs from K. pneumoniae serotypes O1±O5, O8, and O12, contained an aHep-(134)-a-Kdo-(236)-anh-Man fragment at the reducing end, where a-Hep (residue P) is present in the same proportion as in the nonsubstituted core and the O-chain is linked to O-4 of the Kdo residue L (data will be published elsewhere). The presence of the common fragment between the O-chain and core parts of the LPS may be responsible for the interaction with a monoclonal antibody, specifically recognizing Klebsiella LPSs [25,26], since other structural fragments of the LPS are present only in some serotypes or not unique for Klebsiella [26].…”
Section: Discussionmentioning
confidence: 99%
“…Já as linhagens de Klebsiella e Pseudomonas são isoladas com freqüência do trato intestinal de neonatos nos primeiros dias de vida, e vão sendo substituídas por outras espécies, durante a colonização pela microbiota, tornando-se incomuns no trato intestinal de adultos (Bezirtzoglou, 1997 (Luderitz, et al, 1973;Freudenberg, et al,2001). O core também compartilha epítopos entre as diversas bactérias Gram-negativas, o que poderia explicar a reatividade cruzada entre os anticorpos IgM dirigidos às espécies de E. coli, como também à outras espécies de bactérias Gram-negativas analisadas no presente trabalho (Currie, et al, 2001;Zapata-Quintanilla, et al, 2006) As (Rukavina, et al, 2005), que compartilham um epítopo comum localizado no core da molécula do LPS (Trautmann, et al, 1994). (sorotipos 1, 3, 4, 5, 6, 10, 11 e 16), que mostrou eficácia em estudos retrospectivos realizados em pacientes com fibrose cística (Cryz, et al, 1994(Cryz, et al, , 1997Lang, et al, 2004;Langford and Hiller, 1984;Schaadet, al., 1990).…”
Section: Discussionunclassified